Managing Democracy in the Digital Age 2017
DOI: 10.1007/978-3-319-61708-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Sourcing Practices: How Dutch Newspapers Use Tweets in Political News Coverage

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. The publisher, the authors and the editors are safe to assume that the advice and information in this book are believed to be true and accurate at the date of publication. Neither the publisher nor the authors or the editors give a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 172 publications
0
23
0
Order By: Relevance
“…It is not surprising, therefore, that tweets in themselves have become to appear on television and television news (Lefky et al, 2015) and also within newspapers as direct sources of information in themselves (Brands et al, 2018).…”
Section: ) Andmentioning
confidence: 99%
“…It is not surprising, therefore, that tweets in themselves have become to appear on television and television news (Lefky et al, 2015) and also within newspapers as direct sources of information in themselves (Brands et al, 2018).…”
Section: ) Andmentioning
confidence: 99%
“…The free float of easily accessible first-hand information on Twitter has also become an attractive source for journalists, who are operating under financial constraints and time pressure (Lewis, Williams, and Franklin 2008;Schmuck et al 2017). In this context, journalists have been increasingly drawing on information from Twitter in their TV news (Cameron and Geidner 2014;Moon and Hadley 2014), printed news (Brands, Graham, and Broersma 2018;Broersma and Graham 2013;Moon and Hadley 2014;Paulussen and Harder 2014), and online news coverage (Bane 2017;Lecheler and Kruikemeier 2016). Broersma and Graham have shown that journalists frequently use Twitter posts of political actors and directly embed such posts into news stories to "illustrate news events" (2013,450) and "to add flavour to a story" (2013,450).…”
mentioning
confidence: 99%
“…Recent research indicates that journalists seem to be especially prone to embed Twitter posts from right-wing populist actors in their coverage. The reason might be that such posts contain provocative statements, grabbing people's attention and thus contributing to the commercial strategies of news organizations (Brands, Graham, and Broersma 2018).…”
mentioning
confidence: 99%
See 2 more Smart Citations